Penataan Partai Pasca Soeharto: Catatan Kritis RUU Partai Politik - Darwin, Muhadjir (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1998)
This paper discusses critically the proposed law of political party (RUU Partai) Overall, the mentioned law has been advanced than that was applied previously. However, there are still several substantial weaknesses in it which needs some revisions in order to attain the making of independent political parties and democratic life in Indonesia.